RETRACTED: Determination of thermal stress and strain in plates by the direct method - Khamzaev Inomjon; Umarov Elmurad; Khaidarova Ozoda; Abdullayev Shukhratjon; Gapparov Kadirjon (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001